Nicholas Trevet’s Commentary on the Psalms (1317 – c. 1321): A Publishing History - Kujawiński, Jakub (Brepols, 2024)
How did medieval authors publish their works in the age before print? This study seeks to achieve new insights into the publishing strategies of medieval authors by focusing on Nicholas Trevet, an English Dominican friar and Oxford master. Shortly after 1317, Trevet was commissioned by his provincial prior to write a literal commentary on the Psalter. He chose as his reference version the less commonly used Latin translation by Jerome from the Hebrew, and delivered his work before 1321/22. The first book-length examination of Trevet’s commentary, this detailed study traces the ways in which the work was circulated by the author and his proxies. Through a combined analysis of codicological, textual, and historical features of the nine extant fourteenth-century manuscripts, this study identifies contemporary efforts to make Trevet’s work available to readers within and without the Dominican Order, in England and on the Continent. Even during the author’s lifetime the commentary was copied in Paris and reached readers in Avignon and likely in Naples.
The attached file includes the amendments of several infelicities noticed when the book had gone to print.
Keywords: Nicholas Trevet; Psalter; Medieval exegesis; Medieval publishing; Textual criticism; English Dominicans; Manuscript studies; Palaeography